Does Repair of Tetralogy of Fallot Have Age Restrictions? - A. Razinkina; I. Lebid; Ye. Segal; R. Kalashnikova; Ye. Liebied; Y. Kuzmenko; R. Tammo (Ukrainian Journal of Cardiovascular Surgery, 2019)
This publication presents case report of primary non-corrected adult congenital heart disease, tetralogy of Fallot, in forty-seven years old female patient. Clinical and anatomic issues were estimated within postoperative follow-up period and literature concerning surgical repair of tetralogy of Fallot in adult with congenital heart disease was reviewed.The aim. There was presentation the case report of adult patient with tetralogy of Fallot after surgical repair carried out at our Institution, as well as literature review concerning grown-up patients with tetralogy of Fallot in early and late postoperative period.Materials and methods. Female patient, forty-seven years old with grown-up congenital heart disease, tetralogy of Fallot with severe comorbidity.Results. Tetralogy of Fallot was radically repaired with high estimated operative risks. In early postoperative period there was increased exudation through both pleural drainages due to the function of major aortopulmonary collateral arteries. The decision was made to perform interventional closure of major aortopulmonary collateral arteries which enabled to discharge patient within 23 days in satisfactory condition.Conclusions. Presented case report and literature review show that the patient`s age is not a contraindication for repair of tetralogy of Fallot in adults with congenital heart disease. Patients with tetralogy of Fallot usually do not survive until adult age without surgical repair. Our presented case report and literature review show that surgery correction of tetralogy of Fallot in grown-up patients above 40 years of age should be performed in specialized centers experienced in pediatric cardiac surgery and in management of adult congenital heart disease regardless of patient age.